2021
DOI: 10.1007/s42452-021-04629-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and validation of keratinase production by Bacillus aerius NSMk2 in a stirred tank reactor using response surface methodology

Abstract: Keratinase is a robust enzyme that is produced in the presence of keratin substrates. This enzyme has been recognized for its applications in waste management, leather and detergent industries. Our group has isolated a potential keratinase producing strain of Bacillus aerius NSMk2 from poultry dump soil, and its hide dehairing and stain removal applications have been studied. Considering commercial applicability of keratinase, the present study reports the keratinase production in a stirred tank reactor (5 l).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Generally, keratin-degrading efficiency is well reported in several bacteria, especially Bacillus spp., that can thrive on the keratinous biomass as the sole source of nitrogen, and carbon, indicating the secretion of protein-and keratin-degrading enzymes (Nnolim et al, 2020;Bhari et al, 2021;Cavello et al, 2021;Li, 2021). Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, keratin-degrading efficiency is well reported in several bacteria, especially Bacillus spp., that can thrive on the keratinous biomass as the sole source of nitrogen, and carbon, indicating the secretion of protein-and keratin-degrading enzymes (Nnolim et al, 2020;Bhari et al, 2021;Cavello et al, 2021;Li, 2021). Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The species include B. subtilis, B. aerius, B. pumilus, B. cytotoxicus, B. cereus, and B. lichenifomis (Cavello et al, 2021;Li, 2021). The latter is the first commercial keratinase preparation source (Bhari et al, 2021). The current B. paramycoides ZW-5 is another new candidate in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinase production from G. arilaitensis has been proved that the bacterium has higher keratinolytic ability to degrade large biomass. Bhari et al (2021) studies, maximum protein (1.81mg ml ) and amino acids (1.54 mg ml ) were produced at pH 10.5 at 37°C after 72 hrs of incubation in 0.1 N NaOH pre-treated feather. Amuthavalli and Ravi (2023) reported that growth of G. arilaitensis and protein production was higher at alkaline pH 8 and 40°C.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%